Preferensi Konsumen terhadap Label Halal, Kualitas Produk, dan Harga serta Dampaknya terhadap Kepuasan Pengguna Kosmetik - Wulandari, Wuri (Soratekno Publisher, 2025)
The local cosmetics industry in Indonesia is experiencing rapid growth, one of which is marked by the emergence of brands that emphasize ethical, religious, and vegan values such as ESQA. Efforts to face a competitive market, aspects such as product quality, halal label, and price are important factors that influence purchasing decisions. Consumer satisfaction is a major factor in the success of a product in maintaining loyalty amid market dynamics. This study aims to analyze the effect of Product Quality, Halal Label, and Price on Consumer Satisfaction of ESQA cosmetics in Bogor City. The method used is descriptive quantitative with primary data collected through an online questionnaire to 100 respondents drawn using a purposive sampling technique. Data analysis tools used IBM SPSS Statistics 26 through validity and reliability tests, classical assumption tests, and multiple linear regression tests. The results show that partially, Product Quality has no significant effect on Consumer Satisfaction, while Halal Label and Price have a significant effect. Simultaneously, all three variables have a significant effect on Consumer Satisfaction. These findings emphasize the importance of considering price and halal factors in local cosmetics marketing strategies.